(3JMQjQ cJGH XGgQGJ Gdadc dChbdjOSs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3GbdjOSs
(3ChdgG (B:s
(3de jbY Edi ef GdcJGH ZjQ fSNI ai ZGjI GdSbe CcKQgG ef GdJUMja hGdJMQja HMjK de jcf jecf Gdhbha Ydi TF efgG s
(3BNQgG (B:s
(3Je GdcJGH hdeMQc Gdcd GdMeO jbOQ GSJMbGbg s
(3GfXQ CjVkG Gdadc HQbe (B22s
(3ef cJGH (B34 (3MSGHs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B922 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B29 s
Keywords: (3GdQjGVjGJs